Medial Patellofemoral Ligament Reconstruction for Patellar Dislocation: A Systematic Review. Issue 8 (6th August 2014) - Mackay, Nicola D.; Smith, Nicholas A.; Parsons, Nick; Spalding, Tim; Thompson, Peter; Sprowson, Andrew P.
Background: With improved understanding of the biomechanical importance of the medial patellofemoral ligament (MPFL), its reconstruction for patellar dislocation has become increasingly popular. The aim of this systematic review was to critically determine the effectiveness of MPFL reconstruction for patellar dislocation. Hypothesis: MPFL reconstruction for patellar dislocation leads to a low redislocation rate with improved Kujala scores. Study Design: Systematic review; Level of evidence, 4. Methods: A literature search was performed using Embase and Medline (Ovid) databases. Inclusion criteria included first-time and recurrent patellar dislocation, subluxation, or persistent instability with a minimum follow-up of 12 months and documentation of postoperative redislocation rate or Kujala score. The studies were systematically appraised, and a meta-analysis was performed. Results: Twenty-two studies were included: 2 randomized controlled trials, 3 parallel case series, and 17 case series. There were a total of 655 knees in the review, with an age range at time of surgery from 11 to 52 years. The pooled postoperative redislocation rate from all 17 case series showed a mean of 2.44%. The pooled preoperative Kujala scores from 12 case series showed a mean of 51.6 (95% CI, 46.71-56.49). The pooled postoperative Kujala scores from 16 case series showed a mean of 87.77 (95% CI, 85.15-90.39). Conclusion: Although the studies were of low quality, the meta-analysis of 17 case series shows that MPFL reconstruction for recurrent patellar dislocation results in a significant improvement in Kujala scores, a low redislocation rate, and acceptable complication rate. Randomized trials would be needed to draw influences on the superiority of MPFL reconstruction compared with other treatments.